DEVELOPMENT OF ZISWAF LABORATORY MODEL INTEGRATED MB-KM CURRICULUM USING ROWNTREE MODEL (An-Nisbah: Jurnal Ekonomi Syariah, 2023)
Abstrak: Penelitian ini bertujuan untuk melakukan pengembangan model laboratorium yang teirntegrasi dengan kurikulum MB-KM dengan menggunakan pendekatan Model Rowntree. Hasil penelitian ini menunjukkan bahwa pedoman yang dikembangkan sebagai petunjuk pelaksanaan PPL dan KKN MB-KM dikategorikan baik, sehingga dapat digunakan dalam pengembangan model laboratorium ZISWAF Fakultas EKonomi dan Bisnis Islam UIN Fatmawati Sukarno Bengkulu Kata kunci: Model Laboratorium, Kurikulum MB-KM, Model Rowntree Abstract: This study aims to develop a laboratory model that integrates with the MB-KM curriculum using the Rowntree Model approach. The results of this study show that the guidelines developed as guidelines for the implementation of PPL and KKN MB-KM are categorized as good, so that they can be used in the development of the ZISWAF laboratory model of the Faculty of Islamic Economy and Business UIN Fatmawati Sukarno BengkuluKeywords: Laboratory Model, MB-KM Curriculum, Rowntree Model
Keywords: Laboratory Model; MB-KM Curriculum; Rowntree Model